Pengaruh Kualitas Audit, Likuiditas, Solvabilitas dan Profitabilitas Terhadap Opini Audit Going Concern Pada Perusahaan Perdagangan di Bursa Efek Indonesia - Yuni Anggraini; Endang Sri Mulatsih; Feronika Rosalin (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
Companies that want to survive and advance need to develop new strategies. In an economy like this, nothing is always safe from competition, both local and global. Likewise, companies in the trading, service and investment industry sectors listed on the Indonesia Stock Exchange. The formulation of the problem in this research is the development of the influence of audit quality, liquidity, solvency and profitability on going concern audit opinion on trading companies on the Indonesia Stock Exchange for the period 2016-2018 seen partially and simultaneously. The purpose of this study was to see the development of the influence of audit quality, liquidity, solvency, profitability partially and simultaneously. The period used in this research is 2016-2018. The populations in this study are trading companies listed on the IDX. The sample selection used purposive sampling method. Data analysis used to test the hypothesis is to use logistic regression analysis techniques. Based on the results of the study, it shows that research shows that partially, audit quality, liquidity, and solvency do not have a significant effect on going concern audit opinion. Meanwhile, simultaneously, there is at least one variable that has a significant influence on going-concern audit opinion.